2019
DOI: 10.1021/acsami.8b20506
|View full text |Cite
|
Sign up to set email alerts
|

Solving the Water Hypersensitive Challenge of Sulfated Solid Superacid in Acid-Catalyzed Reactions

Abstract: In the past decades, water tolerance has always been the long-pending key issue of sulfated solid superacids (SO4 2–/M x O y ) toward industrial applications. Herein, we report a strategy for the facile coating of a thick tunable hydrophobic layer over SO4 2–/M x O y , which can significantly improve water tolerance, with negligible inhibition on the catalytic performance of SO4 2–/M x O y . Even after being directly immersed in water, the hydrophobic SO4 2–/M x O y can still maintain above 90% of original ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…All the supports and catalysts show typical type IV adsorption isotherms with a noticeable hysteresis loop. This indicates the presence of mesoporous structures in all samples, as is also demonstrated by their pore-size distribution patterns [44,45]. Further, it can be observed from Figure 3a that TiO 2 with different pH values have remarkably different shapes of hysteresis loops.…”
Section: Structural Propertiessupporting
confidence: 58%
“…All the supports and catalysts show typical type IV adsorption isotherms with a noticeable hysteresis loop. This indicates the presence of mesoporous structures in all samples, as is also demonstrated by their pore-size distribution patterns [44,45]. Further, it can be observed from Figure 3a that TiO 2 with different pH values have remarkably different shapes of hysteresis loops.…”
Section: Structural Propertiessupporting
confidence: 58%
“…Interestingly, TiO 2 predecoration could effectively reduce the interaction between sulfate and MnO x ; the SO 4 2− −TiO 2 @ MnO x catalyst showed a strong MnO 2 diffraction peak intensity (Figure 3A). The results of the FT-IR spectra showed that the modification of sulfate and TiO 2 did not change the basic structural unit of MnO 6 in MnO 2 , 38 and the S species was effectively introduced by treating with ammonium sulfate (1125 cm −1 for the symmetric stretching band of S O) 39 (Figure 3B). The sulfate radical treatment of the MnO x catalyst resulted in a diminution in the specific surface area according to the results of the nitrogen adsorption−desorption isotherm and pore size distribution (Figure 3C,D and Table S1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…(2) Improving the water tolerance of catalysts is also important. Water, one of the byproducts of hexose dehydration, poisons solid acids catalysts because of its strong adsorption on the active sites, leading to site blocking and active sites leaching. , A water-tolerant phosphate-immobilized TiO 2 solid acid was reported by Noma et al, where phosphate/TiO 2 was used for glucose conversion. 34% of HMF yield at 49% of glucose conversion was achieved at 120 °C after 4 h. Also, they suggested that the continuous extraction of HMF increased HMF selectivity, even using a high concentration of glucose solution (40 wt %) as the substrate since the side reactions occurred between HMF and intermediates could be prevented.…”
Section: Thermal Catalytic Transformations Of Biomass-derived Glucosementioning
confidence: 99%